Phytochemical Screening and Antioxidant Profile of Syngonium podophyllum Schott Stems: A Fecund Phytopharmakon - Md. Sahab Uddin ,; Md. Sarwar Hossain ,; Md. Tanvir Kabir ,; Imon Rahman ,; Devesh Tewari ,; Mohd. Raeed Jamiruddin ,; Abdullah Al Mamun, (Journal of Pharmacy and Nutrition Sciences, 2018)
Background: Oxidative stress has been shown to play an imperative role in copious disease pathology. Plants are acquaintances of mankind and mainstay for the treatment of oxidative stress linked disorders. Therefore, the objective of the existing study was to assess the phytochemical contents and antioxidant activity of crude methanol extract (CME), n-hexane (NHF), chloroform (CLF), ethyl acetate (EAF) and aqueous (AQF) fractions of Syngonium podophyllum (S. podophyllum) Schott stems. Methods: The S. podophyllum Schott stems extract and its fractions were subjected to phytochemical analysis to detect the presence of alkaloids, carbohydrates, saponins, tannins, resins, flavonoids and steroids. The antioxidant profile was determined by total antioxidant activity (TAA), reducing power activity (RPA) and DPPH (2,2-diphenyl-1-picrylhydrazyl) radical scavenging activity tests and correlated with the estimation of total flavonoid content (TFC). Results: In CME and its fractions of S. podophyllum Schott stems all of the tested phytoconstituents (alkaloids, tannins, resins, flavonoids and steroids) were detected at various concentration except carbohydrates and saponins. In TAA test, highest absorbance (2.18 nm) which is a measure of high antioxidant activity was reported in CME compared to remaining fractions. Likely in RPA test with respect to all fractions similar denouements were found for CME (3.29 nm). In case of DPPH scavenging test, the CME showed highest scavenging activity (77.89 %) having IC50 of 41.02 ?g/ml (P < 0.05) compared to remaining fractions. The antioxidant activity is possibly due to the highest TFC (7.45 mg of GAE/g of dried extract) reported in CME compared to existing fractions. Conclusion: The aforementioned outcomes recommend that CME of S. podophyllum Schott stems can be a possible cradle of plant-derived natural antioxidant and can be used to avert diseases linked with free radicals.